Randomised controlled trial of prolonged treatment in the remission phase of ANCA-associated vasculitis. - Karras, Alexandre; Pagnoux, Christian; Haubitz, Marion; Groot, Kirsten de; Puechal, Xavier; Tervaert, Jan Willem Cohen; Segelmark, Mårten; Guillevin, Loic; Jayne, David; European Vasculitis Society (Elsevier BV, 2017)
OBJECTIVES: A prospective randomised trial to compare two different durations of maintenance immunosuppressive therapy for the prevention of relapse in anti-neutrophil cytoplasmic antibodies (ANCA)-associated vasculitis (AAV). METHODS: Patients with AAV were recruited 18-24 months after diagnosis if they were in stable remission after cyclophosphamide/prednisolone-based induction followed by azathioprine/prednisolone maintenance therapy. They were randomised (1:1) to receive continued azathioprine/prednisolone to 48 months from diagnosis (continuation group) or to withdraw azathioprine/prednisolone by 24 months (withdrawal group). The primary endpoint was the relapse risk, from randomisation to 48 months from diagnosis. RESULTS: One hundred and seventeen patients were randomised and 110 remained to the trial end. At entry, median serum creatinine was 116 μmol/L (range 58-372), 53% were ANCA positive. The percentage of patients presenting with relapse was higher in the withdrawal than in the continuation treatment group (63% vs 22%, p<0.0001, OR 5.96, 95% CI 2.58 to 13.77). ANCA positivity at randomisation was associated with relapse risk (51% vs 29%, p=0.017, OR 2.57, 95% CI 1.16 to 5.68). Renal function, ANCA specificity, vasculitis type and age were not predictive of relapse. Severe adverse events were more frequent in the continuation than withdrawal groups (nine vs three events), but the continuation group had better renal outcome (0 vs 4 cases of end-stage renal disease), with no difference in patient survival. CONCLUSIONS: Prolonged remission maintenance therapy with azathioprine/prednisolone, beyond 24 months after diagnosis reduces relapse risk out to 48 months and improves renal survival in AAV. TRIAL REGISTRATION NUMBER: ISRCTN13739474.
Keywords: ANCA; azathioprine; maintenance therapy; relapse; vasculitis; Adult; Aged; Anti-Inflammatory Agents; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Azathioprine; Creatinine; Cyclophosphamide; Female; Glomerular Filtration Rate; Humans; Immunosuppressive Agents; Kidney Failure, Chronic; Maintenance Chemotherapy; Male; Middle Aged; Prednisolone; Prospective Studies; Remission Induction; Secondary Prevention; Survival Rate; Time Factors